Tingkat Partisipasi Penduduk dalam Menggunakan Layanan Aplikasi Smart city di Kota Surabaya dan Faktor-Faktor yang Mempengaruhinya - Shinta Permata Putri (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The city of Surabaya is one of the reflections of the best smart city in Indonesia. There have been many public service innovations that can be accessed by residents of the City of Surabaya through applications. However, as the best and longest running smart city implementer in Indonesia, it turns out that it has not fully formed the character of a digital community in the city of Surabaya. Not all residents have participated in technology-based smart city innovations in this city. This study aims to see how big the participation rate of urban residents is in using smart city services in the city of Surabaya and what factors influence it. This research is a quantitative study using descriptive statistical analysis techniques. The results of this study indicate that the level of citizen participation in using smart city application services in the city of Surabaya is still relatively low. This result is influenced by two main factors, namely the population factor and also the application factor. In terms of population factors, the use of smart city applications in the city of Surabaya is influenced by motivation, interest/will, and also the awareness of residents in using them. In the application factor, the ease of access to the application and also the quality of the content are factors that influence the use of smart city applications in the city of Surabaya. Going forward, it is felt that the city government still needs to increase the participation of residents in using smart city applications, primarily through promotional/socialization efforts through innovative ideas in order to instill awareness, enthusiasm, involvement, and direct use by residents. In implementing the smart city program going forward, the Surabaya City Government needs to ensure access to applications for all groups of residents, continue with training and increase skills in the use of technology, provide freedom of expression through technology, guarantee its security so that public trust is formed in achieving a digital society.